GLOBAL TEACHER FORUM: ROLE AND IMPACT FOR ENGLISH TEACHER - Danang Dwi Harmoko; Mulyadi Mulyadi; Ahmad Bakhtiar (Research and Development Journal of Education, 2023)
The openness of access to information supported by an adequate infrastructure of technology systems makes barriers between countries disappear. The internet has indirectly united the world's citizens in one network. The internet provides unlimited information that can be utilized by every user, including teachers as educators. In its development, a global teacher forum emerged which was designed as a medium of communication, collaboration, and various other purposes. This study aims to look at the role and impact of global teacher forums on English teachers using a qualitative descriptive method. Data was collected using the SLR (Systematic Literature Review) technique from various sources. To sharpen the findings, researchers also collect data through interviews with English teachers. The results of the study reveal that global teacher forums have an educational role, a teaching resource role, and a collaborative role among various stakeholders. Meanwhile, at the impact level, research reveals that the global teacher forum has an impact on increasing collaboration, teaching quality, strengthening communities, encouraging innovation, and representing the interests of teachers globally